INOVASI GERAK TARI JAIPONGAN DI KLINIK TARI GONDO ART PRODUCTION MENGGUNAKAN METODE KONSTRUKSI JAQUELINE SMITH - Ainun, Nur; Ojang Cahyadi; Selly Oktarini (Program Studi Pendidikan Tari FBS UNJ, 2024)
The process of innovation of Jaipongan dance movement that occurs among the younger generation is more popular than the ketuk tilu style. To keep Jaipongan relevant and popular with this generation, It is important for choreographers to continue innovating the dance. With technology changing so fast, choreographers face a new challenge in their creative process. The constant influx of outside cultures demands that choreographers to be active, creative, innovative to keep pace with the times. The purpose of this research is to find out how the process of creation, motion discovery, and innovation of jaipongan dance that carried out at the Gondo Art Production Dance Clinic using the Jacqueline Smith Construction Method. This research helps dance studios and art institutions understand how dance movements are created and improved. With this knowledge, they can develop new dance works in a more organized way, with stronger ideas and concepts. The research method used is Jacqueline Smith's Construction method. Jacqueline Smith's dance construction consists of 8 stages which are used as a reference for the process of creating dance works. The data collection techniques in this research are observation, interview, literature study and documents. Gondo Art Production Dance Clinic is a dance studio that actively innovates. The style of dance presentation including the main and supporting elements of dance has been innovated by Gondo. This includes everything from the initial ideas and concepts to the dance movements, structure, techniques, music, makeup, costumes, and set design. By revamping all these elements, dance performances become more engaging and different from traditional works, which can help attract younger audiences and keep cultural traditions alive.